Eliciting third person perspectives in social work case discussions: A device for reflective supervision?. (November 2022) - Symonds, Jon; Jorgensen, Sabine; Webb, Joseph; Mullins, Eve; Wilkins, David
Reflective supervision is widely recommended as an effective way to support social workers to think about their practice and to make better decisions. Although previous research has proposed methods of pursuing reflective supervision, little is known about how supervisors attempt this in actual supervision meetings. One proposed method for supervisors is to elicit third person perspectives so that social workers can consider a situation from different points of view. In this article, we examine this method by analysing audio recordings of 12 supervision meetings from one local authority Children and Families Social Work team. Using Conversation Analysis (CA), we explore supervisors' attempts to elicit other people's perspectives, focusing on how such requests were formed and how the social worker responded. We found 35 instances of supervisors attempting to elicit third person perspectives and identified four different ways that supervisors designed these enquiries. Supervisors oriented to two concerns, based on whether they enquired about a perspective that was currently established or projected into the future, and whether the information was verifiable through speech or actions, or imagined based on the other person's thoughts or understanding. We draw on CA work on epistemics and stance to show how these different approaches have implications for what the social worker is expected to know and how both speakers orient to the accountability of the social worker. We conclude by considering the epistemic friction between the design of these enquiries, the relevance of professional accountability and the possibilities for pursuing reflective supervision in practice.